Effect of methacrylic acid monomer on UV-grafted polyethersulfone forward osmosis membrane - Siti Nudra Shafinie, Ab Aziz; Mazrul Nizam, Abu Seman; Syed Mohd Saufi, Tuan Chik; Mohammad, A. W.; Khayet, M. (MDPI, 2023)
UV irradiation is one of the procedures that has been considered for membrane surface graft polymerization. It is commonly utilized for enhancing the wettability of polyethersulfone (PES) membranes. In this research study, the monomer methacrylic acid (MAA) was used for the UV grafting process of a commercial NF2 PES membrane for the preparation of a forward osmosis (FO) membrane. Three different monomer concentrations and three different UV irradiation times were considered. The intrinsic characteristics of both the surface-modified and pristine membranes were determined via a non-pressurized test method. Compared to the NF2 PES, the surface of the modified membranes was rendered more hydrophilic, as the measured water contact angle was reduced considerably from 65° to 32–58°. The membrane surface modification was also confirmed by the data collected from other techniques, such as atomic force microscopy (AFM), field emission-scanning electron microscope (FESEM) and Fourier-transform infrared spectroscopy–attenuated total reflectance (FTIR–ATR). Additionally, the modified membranes exhibited a greater water permeate flux (Jw) compared to the NF2 PES membrane. In this study, the water permeability (A), solute permeability (B) and structural parameter (S) were determined via a two-stage FO non-pressurized test method, changing the membrane orientation. Compared to the FO pressurized test, smaller S values were obtained with significantly high A and B values for the two non-pressurized tests. The adopted method in the current study is more adequate for determining the intrinsic characteristics of FO membranes.